Excursion Guide to the Geomorphology of the Howgill Fells. - Harevy, Adrian (Dunedin Academic Press, 2017)
The Howgills form part of the Yorkshire Dales National Park. The fells are an important study area, especially in relation to modern process geomorphology but also in the context of environmental change. The purpose of this field guide is to give background for students of geomorphology and late Quaternary environmental change.